Effects of Low‐Energy Shockwave Therapy on the Erectile Function and Tissue of a Diabetic Rat Model. (17th December 2012) - Qiu, Xuefeng; Lin, Guiting; Xin, Zhongcheng; Ferretti, Ludovic; Zhang, Haiyang; Lue, Tom F.; Lin, Ching‐Shwun
ABSTRACT Introduction. Low‐energy shockwave therapy (LESWT) has been shown to improve erectile function in patients suffering from diabetes mellitus (DM)‐associated erectile dysfunction (ED). However, the underlying mechanism remains unknown. Aim. The aim of this study is to investigate whether LESWT can ameliorate DM‐associated ED in a rat model and examine the associated changes in the erectile tissues. Methods. Newborn male rats were intraperitoneally injected with 5‐ethynyl‐2‐deoxyuridine (EdU; 50 mg/kg) for the purpose of tracking endogenous mesenchymal stem cells (MSCs). Eight weeks later, eight of these rats were randomly chosen to serve as normal control (N group). The remaining rats were injected intraperitoneally with 60 mg/kg of streptozotocin (STZ) to induce DM. Eight of these rats were randomly chosen to serve as DM control (DM group), whereas another eight rats were subject to shockwave (SW) treatment (DM+SW group). Each rat in the DM+SW group received 300 shocks at energy level of 0.1 mJ/mm2 and frequency of 120/minute. This procedure was repeated three times a week for 2 weeks. Another 2 weeks later, all 24 rats were evaluated for erectile function by intracavernous pressure (ICP) measurement. Afterward, their penile tissues were examined by histology. Main Outcome Measures. Erectile function was measured by ICP. Neuronal nitric oxide synthase (nNOS)‐positive nerves and the endothelium were examined by immunofluorescence staining. Smooth muscle and MSCs were examined by phalloidin and EdU staining, respectively. Results. STZ treatment caused a significant decrease in erectile function and in the number of nNOS‐positive nerves and in endothelial and smooth muscle contents. These DM‐associated deficits were all partially but significantly reversed by LESWT. MSCs (EdU‐positive cells) were significantly more numerous in DM+SW than in DM rats. Conclusion. LESWT can partially ameliorate DM‐associated ED by promoting regeneration of nNOS‐positive nerves, endothelium, and smooth muscle in the penis. These beneficial effects appear to be mediated by recruitment of endogenous MSCs. Qiu X, Lin G, Xin Z, Ferretti L, Zhang H, Lue TF, and Lin C‐S. Effects of low‐energy shockwave therapy on the erectile function and tissue of a diabetic rat model. J Sex Med 2013;10:738–746.